Photo‐Organocatalysis of Atom‐Transfer Radical Additions to Alkenes1. (22nd September 2014) - Arceo, Elena; Montroni, Elisa; Melchiorre, Paolo
Abstract We have found that an organic molecule as simple as p‐anisaldehyde efficiently catalyzes the intermolecular atom‐transfer radical addition (ATRA) of a variety of haloalkanes onto olefins, one of the fundamental carbon–carbon bond‐forming transformations in organic chemistry. The reaction requires exceptionally mild reaction conditions to proceed, as it occurs at ambient temperature and under illumination by a readily available fluorescent light bulb. Initial investigations support a mechanism whereby the aldehydic catalyst photochemically generates the reactive radical species by sensitization of the organic halides by an energy‐transfer pathway.